PENGARUH MODEL PEMBELAJARAN COLEK PIPI (COOPERATIVE LEARNING KO PICTURE AND PICTURE) TERHADAP MOTIVASI DAN HASIL BELAJAR IPA PESERTA DIDIK KELAS VIII SMP MUHAMMADIYAH RAMBAH KABUPATEN ROKAN HULU TAHUN PEMBELAJARAN 2014/2015 - Nasution, Sri Hariyanti; Lestari, Rena; -, Dahlia (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aim of the study was to determine the effect of learning model COLEK PIPI (Cooperative Learning KoPicture and Picture) approach about motivation and the results of SAINS students class VIII SMPMuhammadiyah Rambah Rokan Hulu in Academic Year 2014/2015. This study used quasi-experimental. Thesample of study was VIII-1 class experimen and VIII-2 class control. The result of the study showed that themeans persent of learning motivation of quastiionnaire data was 78,56 with high criteria. The average value ofthe experimental class was 80,57 and 76,28. Analysis result use t-test obtained ttest > ttable it shows that thereâseffect COLEK PIPI modle approach about result of SAINS students.